1998
DOI: 10.4315/0362-028x-61.11.1475
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Listeria spp. in Smoked Fish Products Affected by Liquid Smoke, NaCI Concentration, and Temperature

Abstract: The growth, survival, and death of Listeria monocytogenes were studied in a synthetic medium as a function of temperature, NaCl content, and amount of liquid smoke, and the findings were validated in smoked fish products. The smoke preservative compound was simulated by adding liquid smoke, and the concentration was expressed as phenol concentration. The growth of L. monocytogenes was limited at a temperature as low as 4 degrees C or at a phenol concentration as high as 20 ppm. The predicted values were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 0 publications
2
27
0
1
Order By: Relevance
“…Differential susceptibility to freezing was suggested previously by Destro et al (5), who found that only two PFGE profile groups were present on a frozen shrimp product even though nine different groups were isolated from shrimp in the processing area. Guyer and Jemmi (16) found that the cold-smoking process did not affect L. monocytogenes, although it has been reported that smoke compounds are inhibitory to L. monocytogenes (35,36). Eklund et al (7) observed a decrease in L. monocytogenes populations in surface-inoculated portions treated with smoke and an increase when the organism was injected into the injector of the flesh.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differential susceptibility to freezing was suggested previously by Destro et al (5), who found that only two PFGE profile groups were present on a frozen shrimp product even though nine different groups were isolated from shrimp in the processing area. Guyer and Jemmi (16) found that the cold-smoking process did not affect L. monocytogenes, although it has been reported that smoke compounds are inhibitory to L. monocytogenes (35,36). Eklund et al (7) observed a decrease in L. monocytogenes populations in surface-inoculated portions treated with smoke and an increase when the organism was injected into the injector of the flesh.…”
Section: Discussionmentioning
confidence: 99%
“…Two processes, smoking and freezing, separate the raw material from the sliced material, and both processes are known to reduce bacterial levels (8,35,36). The shift in DNA types during processing could be explained by different abilities of different DNA types to withstand freezing or smoking.…”
Section: Discussionmentioning
confidence: 99%
“…An interaction between salt and phenols has been shown in several studies (Leblanc et al, 2000;Membre, Thurette, & Catteau, 1997;Thurette, Membre, Ching, Tailliez, & Catteau, 1998). The growth inhibitory effect on L. monocytogenes is dependent on the salt concentration, i. e. a mixture of 0.002% phenol and 2 or 3% NaCl had no effect, but the same phenol concentration with 4% NaCl led to a significant reduction in growth (Thurette et al, 1998).…”
Section: Saltmentioning
confidence: 94%
“…Initially, Dalgaard [18] proposed an iterative approach to modelling L. monocytogenes in CSS, combining different kinetic and empirical models. Next, Thurette et al [19] developed a model to predict the behaviour of Listeria as a function of temperature, salt, and amount of liquid smoke expressed as phenol concentration. They validated their model with challenge tests on smoked fish and found agreement between predicted and experimental values within 0.5 log for 60% of the results.…”
Section: Growth Of Listeria Monocytogenes In Lightly Preserved Seafoodmentioning
confidence: 99%